Program Shabāhul Lughah Untuk Pembelajaran Mufradāt Siswa Madrasah Aliyah Negeri 1 Jepara - Lubab, Mohamad Irbabul; Natsir, Muhammad (STIQ Amuntai, 2024)
Al Fikra Islamic boarding school is an educational institution under the auspices of Madrasah Aliyah Negeri 1 Jepara. All students who take superior classes will live in a dormitory (Ma'had) with the aim of forming a generation that is devout in worship, science and technology, as well as improving language skills (Arabic and English) through language activities, namely the shobahul lughah program. Observing this program is very important for implementing the program in learning vocabulary. This research uses a qualitative approach with a case study method, using observation, interviews and documentation as data collection techniques. The results of this research were obtained, 1). Implementation of the shobahul lughah program, students gather in the field to take part in the mufrodat learning that has been determined by the ustadz every week. The implementation time is 07.00-08.00 WIB.,2). The shobahul lughah program method used is the mubasyaroh method to speed up vocabulary mastery and more active learning. 3). Obstacles encountered by educators include: Student discipline and the different abilities of each student. 4). Success factors for the shobahul lughah program include: learning media, skilled abilities of educators, supporting materials and learning motivation.